The Effect of Green Accounting Implementation on Environmental Performance Moderated by Material Flow Cost Accounting - Mahmud, Aisyah; Riza Reni Yenti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Environmental sustainability has become increasingly critical due to global challenges such as climate change, pollution, deforestation, and biodiversity loss. These issues underscore the importance of managing natural resources efficiently to meet human needs while minimizing environmental impact. This study explores the role of Green Accounting and Material Flow Cost Accounting (MFCA) in improving environmental performance, emphasizing their potential to contribute to both sustainability and financial performance. Green Accounting integrates environmental concerns into business strategies, while MFCA focuses on cost-efficient production and waste reduction. The study analyzes secondary data from companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023, using Partial Least Squares (PLS) for data analysis. Findings indicate that Green Accounting significantly enhances environmental performance by promoting resource optimization and waste reduction, which also contributes to financial performance, as reflected in the PROPER program. However, while MFCA supports environmental performance, it does not directly influence the relationship between Green Accounting and environmental outcomes, indicating that the two frameworks, though complementary, serve different purposes. Green Accounting aligns with broader sustainability goals, while MFCA optimizes operational efficiency at the technical level. Together, these approaches provide companies with the tools to balance environmental sustainability and business profitability, ultimately supporting long-term sustainability objectives.